Certified and Uncertified English Teachers Regarding Their Teaching Readiness in Bone Regency: Teachers and Students' Perception-Based - Gunawan Gunawan; Syarifuddin Syarifuddin (Universitas Cokroaminoto Palopo, 2020)
The objective of this research is to find out (1) the perception of the students and teachers in teaching readiness of certified and uncertified English teacher in Bone Regency, and (2) What are the aspects that make the teaching readiness of certified and uncertified English teacher different in Bone Regency. By conducting this research, the researcher explores the data from the students' and teachers' opinions. And the study aims to know the students and teachers' perception in teaching readiness of certified and uncertified English teacher in Bone Regency and the great differences between certified and uncertified English teachers.The method used in this research is descriptive qualitative design. The population of this research consisted of certified and uncertified English teachers and the students in Bone regency. The sample in this research consisted of 8 certified teachers and 8 non-certified teachers and 80 students. The data collected through observation checklist, questioner, and interview. Observation is to find out the data and to support the result analysis of the questionnaires. The interview is intended to support the data gained in the observation.The result of the research showed that certified and uncertified English teachers were different in teaching readiness. Based on the calculation showed that the mean score of the students' perception toward Certificated English Teacher Questionnaire (CET) in teaching readiness is 73.46. And the Non-Certificated English Teacher Questionnaire (NCET) is 66.82%. It indicates that the students' had a Good perception of the Certificated English Teacher Questionnaire (CET) in teaching readiness. And students' had Good enough perception toward Non-Certificated English Teacher (NCET) in teaching readiness. The research results show that there are many aspects that made the teaching readiness of certified and uncertified English teachers different. Those were motivation, teaching experience, classroom situation, professionalism, and teacher welfare.